Hormonal and biochemical factors among chronic liver disease men infected with Toxoplasmosis and some protozoan intestinal parasites - Fingan, Buraq Abdualameer; Al-Warid, Harith Saeed; Al-Sultan, Hayder Jamal (Iraqi Journal of Science, 2025)
Chronic liver disease (CLD) can potentially cause disruptions in the normal functioning of various endocrine organs responsible for producing hormones. As a result, individuals suffering from CLD may experience fluctuations or imbalances in the levels of certain hormones within their bodies. As well as they frequently have suppressed immune systems making them more vulnerable to parasite infections. The primary objective of this study was to investigate the association between Toxoplasma gondii infections and liver function by analyzing the interplay between these parasites and hormones. This study was conducted in Baghdad, Iraq from December 2021 to May 2022. One hundred and twenty male patients with Chronic liver disease (CLD) (age:14-75 years) and 120 control males (age: 24-70 years) participated in this study. Stool and serum samples were collected from all individuals and were then analysed for intestinal protozoan parasites and anti-Toxoplasma antibodies respectively. Hormonal tests were conducted for all participants which included (Cortisol, testosterone, prolactin, insulin, and thyroid-stimulating hormone TSH). Biochemical tests included (Prothrombin time PT, international normalized ratio INR and albumin); liver enzymes were (aspartate aminotransferase AST, alanine aminotransferase ALT, alkaline phosphatase ALP and gamma-glutamyl transferase GGT) and interleukins (Interleukin 13 IL-13 and transforming growth factor TGF). The findings indicate that among the control group participants, 34 individuals, which constitute 28.33% of that group, tested positive for protozoan parasitic infections. In contrast, a higher proportion, 69 individuals or 57.5%, of the participants diagnosed with CLD were found to be positive for protozoan parasites. Four sub-groups were formed in response to prior results: Control-parasites positive, control-parasites negative, CLD-parasite positive and CLD-parasite negative. The status of the protozoan parasites did not affect the hormones levels. The results of liver enzymes showed that parasite positive status was significantly related to all enzymes among CLD patients except the GGT. As well as parasite positive status was not correlated with the other biochemical (PT, INR, and albumin) and immunological parameters (IL-13 and TGF). There was no correlation between the positive status of parasites and cortisol, testosterone, insulin, prolactin, or TSH. The liver enzyme results showed a high correlation (p<0.05) between the presence of parasites and all of the enzymes among CLD patients, with the exception of the GGT enzyme. PT, INR, albumin, and the other biochemical and immunological markers (IL-13 and TGF) did not correlate with the presence of parasites.